α-Glucosidase Inhibitory Activity Of Cucurbitane Derivate Isolated From Methanol Extract Of Momordica charantia L. Leaves - Andi Fikrah Auliya Pamenta (Hasanuddin University, 2019)
Cucurbitane derivative has been isolated from methanol extract of the leaves of bitter melon (Momordica charantia). Purification of methanol extract using vacuum column chromatography method using n-hexane: ethyl acetate as the mobile phase was obtained a white powder isolate. This isolate was elucidated to obtain chemical structures based on spectroscopic data (FT-NMR, FT-IR, and LC-MS/MS) and resulted a cucurbitane derivate, namely momordicine I. The MeOH extract and the isolate were evaluated for α-glucosidase inhibitory effect. Both MeOH extract and momordicine I showed moderate activities with %inhibition 27.34% and 15.79 % at 100 µg/mL repectively.